(untitled) (Journal of Business Management and Accounting, 2014)
In Saudi Arabia, public organizations have been associated with poor management and performance. Little is understood about the reasons for such poor performance. Skilled and trained leaders are required to sustain the performance of these organizations. This paper focuses on the effect of leadership styles on the performance of Saudi Arabia public organizations. Cross-sectional data of 400 employees working in 16 ministries under the Saudi Arabia Government were obtained. The validity and reliability of the measurement and structural model were tested. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to test the study hypotheses. The result of PLS-SEM analysis indicated a significant effect of leadership style on the organizational performance at the 0.01 level of significance. Leadership styles play a critical role in improving organizational performance in Saudi Arabian public organizations. Future research is recommended to explore further the predictors affecting the performance of public organizations in Saudi Arabia.